Covid-19 Pandemic and Beachside Businesses: A Curse or a Blessing in Disguise? - Apreh Siaw, Gladys; Apreh Siaw, Nicholas; Agbenyeke, Lucy Eyram - (International Journal of Scientific Research and Management (IJSRM), 2025)
The Covid-19 pandemic has had a profound impact on businesses worldwide, with the tourism and hospitality sector being particularly affected. This study investigates how managers of beachside businesses in Cape Coast, Ghana, perceive the pandemic's impact on patronage and health and safety practices. Using a qualitative approach, semi-structured interviews were conducted with 12 managers, and thematic analysis was employed to analyze the data. The findings reveal three primary themes: a significant decline in patronage due to restrictions and fear of infection, the adoption of enhanced health and safety practices to comply with mandates and reassure customers, and mixed perceptions of the pandemic as either a curse due to financial losses or a blessing in disguise due to opportunities for innovation and improvement. The study concludes that the pandemic has been both a curse and a blessing for these businesses, with recommendations for sustaining health and safety improvements, exploring digital innovations, and providing targeted policy support to foster recovery and resilience.